Pengaruh Total Quality Management Dan Reputasi Perusahaan Terhadap Produktivitas Karyawan PT. Mark Dynamics Indonesia Tbk. Tanjung Morawa - Siska Handayani; Indra Utama (Jurnal Akuntansi, Manajemen dan Ekonomi Digital, 2022)
The title of this research is “The Influence of Total Quality Management and Company Reputation on Employee Productivity of PT. Mark Dynamics Indonesia Tbk". The purpose of this study was to determine whether there is an effect of Total Quality Management and Company Reputation on the Employee Productivity of PT. Mark Dynamics Indonesia Tbk". The data used in this study is primary data with the research instrument in the form of a questionnaire. The population used is 500 employees of PT. Mark Dynamics Indonesia Tbk, using random sampling of as many as 84 respondents. The method used in this research is the descriptive quantitative method. The data analysis technique uses multiple linear regression analysis with regression equations Y = 1.582 + 0,1324X1 + 0,373X2  + e. Partial test results (t) obtained are 22,475 for Total Quality Management and 11,889 for Company Reputation. While the results of the simultaneous F test obtained are 1485,545. And the results obtained in this study showed an R2 value of 97.3%, so it can be concluded that Total Quality Management and Company Reputation have a positive and significant effect on the Employee Productivity of PT. Mark Dynamics Indonesia Tbk and the remaining 2.7% are influenced by other factors.Keywords: Total Quality Management, Company Reputation, And Employee Productivity